Employee motivation: a comparison between Malaysia and UAE - Islam, Rafikul; Barhem, Belal (Malaysian Institute of Management, 2007)
Employee motivation is crucial for organizations to attain competitive advantage in the marketplace. Over the decades, industrial psychologists have developed theories that are purported to help organizational managers to motivate their employees. Employee motivation is also proved to be influenced by the local/national culture. In order to know the motivating factors, in the present work, on a personal contact basis, we conducted surveys in two countries, namely Malaysia and UAE. Altogether 505 and 335 employees working in various organizations in Malaysia and UAE, respectively took part in the survey. The results are synthesized and prioritized lists of motivating factors are obtained for both the countries. A detailed comparison on the findings on the two countries is made. Managerial implications of the findings are highlighted and the results of the study are expected to provide managers in developing effective motivation programs.